Improving Student Life Skills and a Green Environment at Darul Faqih Middle School through Aquaponic Technology Training: Peningkatan Life Skill Santri dan Lingkungan Hijau di SMP Darul Faqih melalui Pelatihan Teknologi Aquaponik - Umi Afdah; Yekti Sri Rahayu; M. Adri Budi Sulistyo; Sophie Agustina; Amelia Widiyatna Indrasari (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
This community service program seeks to solve the problem of limited skills of students at Darul Faqih Indonesia Middle School in creating a green environment in the school area. The solution offered is improving the skills of students and the role of Musrifah as household managers of Islamic boarding schools through training in the application of aquaponic technology and its arrangement in the classroom environment. The method of implementing the activities is in the form of training, mentoring, and direct practice of aquaponic technology which combines cultivating plants and catfish in buckets, as well as maintaining them until harvesting. The results of the implementation of the activity showed that there was an increase in the skills of santri and Musrifah in applying hydroponic vegetable cultivation technology, ornamental plants and aquaponic fish. Some of the aquaponic technology learning practices that students are able to develop are techniques for cultivating vegetable seeds in rockwool media, planting and maintaining vegetable seeds and ornamental plants, placing indoor installations, and aquaponic catfish cultivation technology. Placing aquaponic installations of ornamental plants and catfish in rooms with limited lighting conditions is a solution in creating a green environment in areas within the school. Meanwhile, the placement of hydroponic installations for vegetable plants and catfish in semi-outdoor areas provides a green environment in the school terrace area. It is hoped that the green environment built in the cottage environment can support a beautiful, comfortable, beautiful and sustainable teaching and learning environment.